Methylprednisolone Decreases Mitochondria-Mediated Apoptosis and Autophagy Dysfunction in Hepatocytes of Experimental Autoimmune Hepatitis Model via the Akt/mTOR Signaling - Fan, Xiaoli; Men, Ruoting; Wang, Haoran; Shen, Mengyi; Wang, Tingting; Ye, Tinghong; Luo, Xuefeng; Yang, Li (Frontiers in Pharmacology, 2019)
Autoimmune hepatitis (AIH) is characterized by massive immune cell-mediated hepatocyte destruction. Glucocorticoids, particularly methylprednisolone (MP), are the most effective treatment for AIH; however, the mechanism underlying the effects of glucocorticoid treatment has not been fully elucidated. The present study explored the effects of MP on damaged hepatocytes in mice with concanavalin A (ConA)‑induced experimental autoimmune hepatitis (EAH). C57BL/6 mice were divided into three groups: a normal control group (injected with normal saline), a ConA (20 mg/kg) group, and a ConA + MP (3.12 mg/kg) group. The serum levels of liver enzymes, cytokines, activated T cells and apoptosis‑ and autophagy‑associated marker proteins were determined 12 h after ConA injection. Human hepatocyte cell line LO2 was used to verify the effects of ConA and MP in vitro. MP treatment significantly aggravated inflammatory reactions in the serum and liver tissues and activated the Akt/mTOR signaling pathway to inhibit apoptosis and autophagy in hepatocytes in vivo. Transmission electron microscopy (TEM) revealed fewer autophagosomes in the MP-treated group than in the ConA-treated group. MP treatment obviously suppressed apoptosis and mitochondrial membrane potential (ΔΨm) loss in hepatocytes in vitro. Furthermore, ConA treatment increased the levels of LC3-II, p62/SQSTM1 and Beclin-1, while bafilomycin A1 did not augment the levels of LC3-II. MP treatment decreased the levels of LC3-II, p62/SQSTM1 and Beclin-1 and upregulated the levels of phosphorylated (p)-Akt and p-mTOR. In conclusion, MP ameliorated mitochondria-mediated apoptosis and autophagy dysfunction in ConA-induced hepatocyte injury in vivo and in vitro via the Akt/mTOR signaling pathway